Earthquake Disaster Preparedness Among Students of SMAN 1 Lembar-West Lombok - Dr. Kosim., M.Si Dr. Kosim., M. Si. (Postgraduate Program, University of Mataram, 2026)
The 2018 West Nusa Tenggara earthquake devastated homes, causing numerous casualties and economic paralysis, particularly in the affected areas. It is impossible to predict when this disaster will occur or how severe the potential hazards will be. Therefore, humans can only act to minimize the risk of damage caused by the disaster. A community service activity conducted on May 27, 2023, among students at SMAN 1 Lembar aimed to educate and conduct an evacuation simulation regarding earthquake hazards so that participants would learn about earthquake preparedness. Forty-nine students participated in the activity. The students were given a questionnaire containing knowledge about earthquakes and evacuation procedures during an earthquake while at school. The overall content of the questionnaire indicated students' preparedness for earthquake disaster mitigation. The data from the scores were converted to an X value on a scale of 100. The lowest score was 54.5 and the highest was 90.9. While the average value (M) is 77.3 with a standard deviation (SD) of 4.5. Through this statistical data, the value of student preparedness for earthquake disaster mitigation is made into three categories, namely the low category with the criteria of data value X < M – SD, the medium category with the criteria M – SD < X < M + SD and the high category with the criteria X> M + SD. Based on the data analysis, the low category is 24%, the medium category is 39% and the high category is 37%. The conclusion of this activity, indicates that through the socialization and simulation of earthquake disaster mitigation, that students of SMAN 1 Lembar – West Lombok who participated in the socialization of disaster mitigation around 76% are expected to have preparedness for earthquake disaster mitigation.